2006
DOI: 10.1021/om050789s
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear Ruthenium Complexes Bearing Dicarboxylate and Phosphine Ligands. Acceptorless Catalytic Dehydrogenation of 1-Phenylethanol

Abstract: Reaction of RuH 2 CO(PPh 3 ) 3 with tetrafluorosuccinic acid at 100°C gave rise to the formation of the dinuclear bis(tetrafluorosuccinate)-bridged Ru(II) complex 2, containing two water ligands. Exchange of the PPh 3 in complex 2 with various diphosphine ligands afforded a series of analogous complexes 3. Reaction of the latter with 1-phenylethanol at 130°C or with 2-propanol/Et 3 N at room temperature furnished the dinuclear dihydrido-bridged Ru(II) complexes 4. Complexes 2 and 4 were characterized by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Therefore, the development of selective catalysts which can work at low temperature is of crucial importance for the application of this relevant sustainable transformation. Monocarbonyl Ru complexes, namely the Dobson catalyst Ru(OCOCF 3 ) 2 (CO)(PPh 3 ) 2 and [Ru(μ‐O 2 CC 2 F 4 CO 2 )(CO)(PP)] 2 (PP=diphosphane), are active catalysts for alcohol dehydrogenation, which is the first step of the catalytic N‐alkylation. Recently, the in situ‐generated complex Ru(OCOCF 3 ) 2 (CO)(PPh 3 ) 2 /( R )‐BINAP has been found as active catalyst for the asymmetric C−C coupling between olefins and primary alcohols .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of selective catalysts which can work at low temperature is of crucial importance for the application of this relevant sustainable transformation. Monocarbonyl Ru complexes, namely the Dobson catalyst Ru(OCOCF 3 ) 2 (CO)(PPh 3 ) 2 and [Ru(μ‐O 2 CC 2 F 4 CO 2 )(CO)(PP)] 2 (PP=diphosphane), are active catalysts for alcohol dehydrogenation, which is the first step of the catalytic N‐alkylation. Recently, the in situ‐generated complex Ru(OCOCF 3 ) 2 (CO)(PPh 3 ) 2 /( R )‐BINAP has been found as active catalyst for the asymmetric C−C coupling between olefins and primary alcohols .…”
Section: Methodsmentioning
confidence: 99%
“…These spectral features are comparable to the RuH(CNN)(dppb) system . It is worth pointing out that, although the dinuclear hydride complex [Ru(μ‐H)(CO)(BINAP)] 2 [O 2 CC 2 F 4 CO 2 ] has been described as a resting‐state species for alcohol dehydrogenation, the mononuclear species RuHX(CO)(PP) (X=Cl, carboxylate) has been postulated to play a key role in the catalytic cycles of alcohol dehydrogenation and C−C coupling reactions …”
Section: Methodsmentioning
confidence: 99%
“…[4] For the preparation of carbonyl compounds, Hulshof and co-workers found that the Robinson catalyst [5] and the related system [Ru(m-OCOC 2 F 4 OCO) 2 (CO)-(diphosphane)] 2 [6] can be employed for the acceptorless dehydrogenation of secondary alcohols, affording ketones in good yields. Adair and Williams described the dehydrogenation of secondary alcohols using the Grubbs catalyst [RuCl 2 2 /PPh 3 system.…”
Section: )A C H T U N G T R E N N U N G (Pph 3 )mentioning
confidence: 99%
“…It would be of great economical and ecological importance to develop processes, which take place at milder conditions and produce less waste. With this view, several transition metalcatalyzed hydrogen transfer processes involving oxidation of alcohols [5,6], and oxidation of alcohols without oxidant and hydrogen acceptor [7,8], have been reported. In nature, enzymes can perform selective oxidation reactions at mild conditions [9].…”
Section: Introductionmentioning
confidence: 99%